Meningkatkan Minat Belajar Siswa Melalui Penerapan Game Based Learning dalam Kurikulum Merdeka di SMA Batik 2 Surakarta - Al Fiatul Ula; Gianni Nur Fadilah; Aisyah Nurrusyifa (Lembag, 2025)
This study aims to analyze the use and implementation of the Game Based Learning (GBL) model in enhancing students’ interest in learning Economics within the Merdeka Curriculum. The research employed a descriptive approach through interviews and classroom observations involving both students and teachers. The findings indicate that GBL is applied as an interactive learning strategy that helps simplify the understanding of economic concepts, increases student engagement, and builds a more enjoyable and stimulating learning atmosphere. The use of game elements in the learning process encourages active participation and supports students in developing better focus during lessons. In addition, the implementation of GBL is considered effective and relevant to the demands of 21st-century learning, where creativity, critical thinking, and collaboration play essential roles. Based on the results, this study recommends strengthening school facilities and providing teacher training to further maximize the effectiveness of GBL in the learning process.